Estudo de estratégias clássicas de regulação de velocidade de hidrogeradores - COSTA, William Ribeiro (2018)
This work will treat about dynamic stability of power systems, more specifically about the main strategies of speed regulating of hydro generators. The models will be seen: an isolated system powering a load and an interconnected system with two generators feeding different loads. Analyses will be performed considering small perturbations in the load demand and the main considerations are related to the dynamics of power and speed in steady-state. Several situations will be simulated using the Simulink toolbox of Matlab.